Evaluation of amplified rDNA restriction analysis (ARDRA) for the identification of Mycoplasma species - Stakenborg, Tim (BioMed Central, 2005)
BACKGROUND: Mycoplasmas are present worldwide in a large number of animal hosts. Due to their small genome and parasitic lifestyle, Mycoplasma spp. require complex isolation media. Nevertheless, already over 100 different species have been identified and characterized and their number increases as more hosts are sampled. We studied the applicability of amplified rDNA restriction analysis (ARDRA) for the identification of all 116 acknowledged Mycoplasma species and subspecies. METHODS: Based upon available 16S rDNA sequences, we calculated and compared theoretical ARDRA profiles. To check the validity of these theoretically calculated profiles, we performed ARDRA on 60 strains of 27 different species and subspecies of the genus Mycoplasma. RESULTS: In silico digestion with the restriction endonuclease AluI (AG^CT) was found to be most discriminative and generated from 3 to 13 fragments depending on the Mycoplasma species. Although 73 Mycoplasma species could be differentiated using AluI, other species gave undistinguishable patterns. For these, an additional restriction digestion, typically with BfaI (C^TAG) or HpyF10VI (GCNNNNN^NNGC), was needed for a final identification. All in vitro obtained restriction profiles were in accordance with the calculated fragments based on only one 16S rDNA sequence, except for two isolates of M. columbinum and two isolates of the M. mycoides cluster, for which correct ARDRA profiles were only obtained if the sequences of both rrn operons were taken into account. CONCLUSION: Theoretically, restriction digestion of the amplified rDNA was found to enable differentiation of all described Mycoplasma species and this could be confirmed by application of ARDRA on a total of 27 species and subspecies.